Reproductive Capability of English Roses in Conditions of Forest-Steppe of Ukraine - Gordiienko, Dariia; Rubtsova, Olena; Chizhankova, Valentina; Buidina, Tetyana; Sokolova, Olga; Vaskivska, Svitlana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Reproductive capability of English roses has not been well studied experimentally. But these researches are important to rose hybridization because cultivars often have low fertility. In the article offered morphological indicators of reproductive success and evaluate assess the reproductive potential of 7 cultivars of English roses from collection of 55 varieties. The quantitative indicators of the generative organs of the studied varieties are estimated according to the methodological instructions given in the Atlas of the morphological features of the varieties of roses. Biometric indicators were investigated: number of petals, stamens and pistils. Part of the stamens turned into petals, and therefore the amount of pollen decreased. As a result of studying the flower structure of English roses, it was determined that their inherent feature is the phenomenon of trimorphous geterostyly, namely there are three forms of the flower of cultivars: short-, medium- and macro-styles. Potential and real seed productivity is identified. The highest number of seeds in the hip is recorded in cultivar origin. Seed production shows that fertilization has occurred. The data should be used when planning rose breeding, namely for the selection of parent plants: the cultivars with well-knotted seeds should be used as seed plants.